Development and/or change of the notion of permanent object and operative causality: Empirical evidence in the frst year of life (2013)
This study examines the notion of permanent object during the first year of life, taking into account the controversy of two approaches about the nature of change: developmental change and cognitive change. Using a longitudinal/cross-sectional design, tasks adapted of the subscale of permanent object and operative causality of the Uzgiris-Hunt Scale (Uzgiris and Hunt, 1975) (Uzgiris & Hunt, 1975) were presented to 110 infants of 0, 3, 6 and 9 months-old, which reside in three cities of Colombia. The results showed three types of strategies: (a) Not resolution; (b) Exploratory and (c) Resolution, which follow different trajectories in children's performance. This allows affirming that adaptive conquests of the cognitive development stay together with the variety of strategies. Using strategies reveals adjustments and transformations of action programs that consolidate the notion of permanent object not necessarily with age, but with self-regulatory processes. Empirical evidence contributes to the understanding of the relations between the emergence of novelty in the development and performance variability.